The Settlement Survey of Tikal : Tikal Report 13 - Puleston, Dennis Edward, 1940-1978 (Book collections on Project MUSE., 1983)
This volume is an essential reference in the study of Classic Maya settlement patterns. Maps of four cardinally oriented strips, each extending 12 km from central Tikal, document the survey area. In addition to these major overall maps (at 1:5000), a number of 1:2000 maps cover the many relatively smaller sites. The accompanying text explains the strategy, procedures, and theoretical considerations of mapping systems.